2008
DOI: 10.1111/j.1467-9280.2008.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Which Thoughts Count? Algorithms for Evaluating Satisfaction in Relationships

Abstract: Individuals differ in both their motivation to obtain incentives in their relationships (approach goals) and their motivation to dampen the threats in their relationships (avoidance goals). When evaluating relationship satisfaction, individuals with strong approach goals should weigh positive features in their relationships more heavily than do individuals low in approach goals, and individuals with strong avoidance social goals should weigh negative features more than do individuals with weaker avoidance soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 25 publications
(29 reference statements)
4
88
0
3
Order By: Relevance
“…These findings were found across three studies using different methods (i.e., in scenario studies and in actual social interactions involving acceptance or rejection). In general, the present findings are in line with previous research showing that social approach motives are particularly predictive in positive social situations and social avoidance motives particularly predictive in negative social situations (Gable & Poore, 2008;Nikitin et al, 2012;Strachman & Gable, 2006). Thus, social approach motives are related to the positive impact of positive social outcomes, but do not buffer the effects of negative outcomes, whereas social avoidance motives are related to the negative effects of negative social outcomes, but do not affect the experience of positive outcomes.…”
Section: Differential Associations Between Social Approach and Avoidasupporting
confidence: 92%
See 1 more Smart Citation
“…These findings were found across three studies using different methods (i.e., in scenario studies and in actual social interactions involving acceptance or rejection). In general, the present findings are in line with previous research showing that social approach motives are particularly predictive in positive social situations and social avoidance motives particularly predictive in negative social situations (Gable & Poore, 2008;Nikitin et al, 2012;Strachman & Gable, 2006). Thus, social approach motives are related to the positive impact of positive social outcomes, but do not buffer the effects of negative outcomes, whereas social avoidance motives are related to the negative effects of negative social outcomes, but do not affect the experience of positive outcomes.…”
Section: Differential Associations Between Social Approach and Avoidasupporting
confidence: 92%
“…Accordingly, avoidance motives are associated with a heightened sensitivity to negative information, whereas approach motives are related to a heightened sensitivity to positive information, but not vice versa (e.g., Derryberry & Reed, 1994;Gomez & Gomez, 2002;Higgins & Tykocinski, 1992;Strachman & Gable, 2006). For example, Gable and Poore (2008) investigated what information people base their evaluation of relationship satisfaction on. They found that people with strong social approach motives based their evaluation on the presence or absence of positive information, whereas people with strong social avoidance motives based their evaluation on the presence or absence of negative information.…”
mentioning
confidence: 99%
“…Starting the day after the baseline session, we scheduled a daily questionnaire to be sent to participants via email with instructions to complete it that night. However, responses were considered timely if completed by 12:00 pm the following day (Gable & Poore, 2008), with timeliness verified via electronic time stamps. When participants did not complete a diary on time, we sent an email to inquire about any difficulties they might be having.…”
Section: Daily Diariesmentioning
confidence: 99%
“…First, the couples we sampled varied widely in relationship duration and age, adding generalizability to prior studies on similar phenomena that have relied on younger couples (e.g., Gable & Poore, 2008;Impett et al, 2010;Impett et al, 2008).…”
Section: Strength Limitations and Future Directionsmentioning
confidence: 99%
“…A stronger avoidance orientation covaries with better memory for negative information (Strachman & Gable, 2006), and while individuals higher in avoidance orientation weigh thoughts of security more heavily than those low in avoidance orientation, individuals higher in approach orientation weigh thoughts of passion more heavily compared to those low in approach orientation (Gable & Poore, 2008). Thus, avoidance orientation affects cognitive processes such as memory and the interpretation of ambiguous information and affective cues; this heightened focus on negative outcomes or events, which is inherent in avoidance regulation, is in turn "likely to elicit and sustain threat appraisals, anxiety and self-protection processes, as the individual is incessantly reminded of aversive possibilities" (Elliot & Sheldon, 1998, p. 1283.…”
Section: Running Head: Avoidance and Negative Communicationmentioning
confidence: 99%